Improvement Of Working Condition Through A Participatory Ergonomics Approach Decrease Low Back Pain Complaints And Increase The Productivity Of Tailors - Fadma Putri; I Putu Gede Adiatmika; I Made Krisna Dinata (Eduvest - Journal of Universal Studies, 2021)
Tailors work in a static position and bend over with a relatively long duration of workPostural muscle load on tailors results in the risk of complaints of low back pain which affects the productivity of tailor. The aim is to know the effect of improving working conditions through a participatory ergonomics approach to reduce low back pain complaints and increase tailor productivity.The method uses of experimental research with treatment by subject design, involving 9 samples selected by simple random sampling. Period 1 sample is working with conventional working conditions. Period 2 samples worked with improving working conditions through a participatory ergonomics approach. Washing out period and adaptation are given between the two periods. Complaints of low back pain were measured by the Oswestry Disability Index, while productivity was based on a comparison between the number of stitches/day and the score for complaints of low back pain per working time. The results showed that improving working conditions through a participatory ergonomics approach had a significant effect (p < 0.05). There was a decreasing in low back pain by 11.87% from an average of 48.67±1.73 to 42.89±1.76 and an increasing in productivity of 42.10% from an average of 0.038±0.004 to 0.054±0.005.